(untitled) (The Strategic Review for Southern Africa, 2020)
Terrorism is increasingly becoming a major threat to global peace and security given the changing geopolitical terrain on which it is enacted. This has given rise to new metageographies of geopolitics characterised by intricate operational networks used by terrorists to achieve their goals. Closely linked to the growing problem of terrorism is globalisation, which has altered our understanding of the geopolitical behaviour of states in the international system. Although it has not removed state boundaries, globalisation has also opened states up for flows and exchanges. Terrorist groups are part of these flows and they have been able to exploit this new geopolitical situation through the recruitment of migrants and the development of terrorist networks across state boundaries. Boko Haram in Nigeria is a typical example of a terrorist group that has evolved into a sophisticated terrorist sect with illegal migrant recruits and transnational networks through the changing geopolitics brought on by globalisation. This article therefore explores the metageography of Boko Haram in Nigeria and how this is aided by migration and social networking occasioned by globalisation. It does so by examining the various structures of the sect, and the nature of its networks. By using the mutual or collective interest theory, the article attempts an explanation of how Boko Haram operates as a group with linkages to diverse transnational terrorist groups bound by a common group interest; anti-Westernisation and global Islamisation. It concludes that Boko Haram has developed a decentralised but sophisticated transnational network which makes it even more difficult for the Nigerian government to deal with its spread.